2021
DOI: 10.1039/d1cc03376j
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and luminescence of trinuclear lanthanide based supramolecular circular helicates

Abstract: A series of trinuclear lanthanide circular helicates [Ln3L3]Cl3 have been synthesized via supramolecular subcomponent self-assembly. Photophysical studies demonstrate that the unique helical bis-tetradentate 1,29-dialdehyde ligand L2- could serve as an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Slight differences in the lengths of the M–O bonds in compounds 3 , 4 , and 5 result from the different lengths of the ionic radii of the lanthanide cations. These values correspond to the length of the M–O bonds found in the compounds Eu, Dy, and Er described by Huang et al and Tb, Dy, Ho, and Er reported by Li et al, which contain M–O–Ph fragments.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Slight differences in the lengths of the M–O bonds in compounds 3 , 4 , and 5 result from the different lengths of the ionic radii of the lanthanide cations. These values correspond to the length of the M–O bonds found in the compounds Eu, Dy, and Er described by Huang et al and Tb, Dy, Ho, and Er reported by Li et al, which contain M–O–Ph fragments.…”
Section: Resultssupporting
confidence: 82%
“…Slight differences in the lengths of the M−O bonds in compounds 3, 4, and 5 result from the different lengths of the ionic radii of the lanthanide cations. These values correspond to the length of the M−O bonds found in the compounds Eu, Dy, and Er described by Huang et al 44 and Tb, Dy, Ho, and Er reported by Li et al, 45 lanthanide compounds described by Li et al, 45 in which three chlorine anions coordinate to the metal cation. Intramolecular hydrogen bonds additionally stabilize the structures of 3−5 coordination entities.…”
Section: ■ Introductionsupporting
confidence: 76%
“…Cages composed of ligands bearing dynamic covalent bonds, which form in situ by subcomponent self-assembly, have grown in interest over the last decade. [66][67][68][69][70][71][72][73] These systems enable cage-to-cage transformations to occur via exchange of aldehyde or amine subcomponents, rather than complete ligands. Such processes are driven by the formation of more thermodynamically stable complexes when new subcomponents are introduced, driven by the difference in electronic and steric properties of various subcomponents, or the chelate effect.…”
Section: Transformations Induced Through Subcomponent Exchangementioning
confidence: 99%
“…(D) Lanthanide templated self‐assembly of circular helicates [Ln 3 L 56 3 ] 3+ . Reproduced with permission 186 . Copyright 2021, Royal Society of Chemistry.…”
Section: Polynuclear Lanthanide Complexes: Discrete Oligomersmentioning
confidence: 99%